RANCANG BANGUN SISTEM INFORMASI PERENCANAAN PERSEDIAAN BARANG - Wijaya, Andy; Arifin, Moch.; Subiyanto, Tony (Jurnal JSIKA, 2013)
: As a company that acts as a distributor of goods, good inventory management is one of the important factors for the success of the company. Distributors must have a good inventory management to meet the demands of its customers. The problem that often occurs when there is no good inventory management is the company will experience a shortage or excess inventory so a loss. Problems that occur due to the amount of customer demand is uncertain, so the company had difficulty in determining the minimum stock of each item, determine when reordering, and determine how many goods orders accordingly. In order to overcome the problems occurred, the company requires an inventory planning system that can determine the minimum stock, reorder time and the optimal number of reservations. The solution is to make inventory planning information system using the Economic Order Quantity (EOQ). With the EOQ method, it can be determined that the optimal number of bookings and minimize storage costs and ordering goods, and reorder point as a reference for companies to know when to order the goods. Based on the experiments performed can be concluded that the system can meet the needs of the other applications can generate output that can be used as a reference for the company in order goods inventory.   Keyword: EOQ, Inventory